Perceived effectiveness of one-minute preceptor in microskills by residents in dental residency training at National Dental Centre Singapore - Marianne Meng-Ann Ong; Mimi Yow; Jestina Tan; Scott Compton (Proceedings of Singapore Healthcare, 2017)
Background: The National Dental Centre Singapore (NDCS) has collaborated with the National University of Singapore’s Division of Graduate Dental Studies to provide supervised clinical training in the five dental specialties for residents since the early 1990s. Faculty were first introduced to the one-minute preceptor (OMP) in microskills through in-house workshops held from May to August 2014. Purpose : The aim of this study was to assess if a OMP faculty workshop impacts residents’ perceptions of clinical teaching in NDCS. Methods : First- and second-year residents were asked to rate their perceptions of the quantity and quality of clinical teaching, and the adequacy of the five OMP microskills performed by faculty before and one month after the OMP workshops. Data were analysed using descriptive statistics and non-parametric statistical tests. Results : A total of 37 NDCS clinical faculty participated in the OMP workshops and 34 residents participated in the pre- and post-workshop survey. The short-term impact of the OMP faculty workshop revealed minimal effect on residents’ perceptions of the clinical teaching in both quantity and quality. Conclusion : A one-time OMP workshop for faculty members does not substantially improve residents’ perceptions of the quality or quantity of clinical teaching. The results of this study indicate that the effort to improve clinical teaching by faculty must be a sustained effort. Future studies should investigate the barriers to faculty members’ performance of the OMP microskills.